Political scandals, media systems, and ideological polarization: the case of the emeritus King Juan Carlos I - Azahara Ortiz-González; Rosa Berganza (Communication & Society (Formerly Comunicación y Sociedad), 2022)
Research on scandals is a privileged way to explore jointly media and political systems, and the links between them. In this article, we explore how the coverage of political corruption in digital native and paper newspapers has the characteristics of politically oriented scandals (Mancini, 2019), which are more common in polarized pluralist systems, like the Spanish one. To do so, we have studied the scandals related to the former King of Spain, Juan Carlos I. In the research, we have analyzed the evolution of media coverage on the topic between July 1, 2014, and March 1, 2021 in three different paper newspapers (El País, El Mundo and ABC). During this period, 889 journalistic pieces were published in these three newspapers. Also, we have conducted a quantitative and qualitative analysis of a sample of 334 pieces from the last year covered by the research (2020-2021) on El País, El Mundo and ABC and on digital natives El Español and elDiario.es. The results show a political instrumentalization of the scandal, media partisanship (the media support some political parties’ positions) in El País, elDiario.es and ABC; and ideological polarization (analyzed content presents two politically opposed groups) in ABC and elDiario.es.